The Effect of Job Pressure and Task Complexity on Performance with Resilience Ability as Moderator - Maxi Yehuda; Andre Manuel; Fransisca Imanuel (Primanomics : Jurnal Ekonomi & Bisnis, 2024)
Indonesia has moved up to the 33rd position globally in terms of performance competitiveness, compared to the 43rd rank in the previous year. This significant improvement indicates that Indonesia possesses considerable performance competitiveness potential. However, to maintain and further enhance its global competitiveness, it is crucial for the country to focus on the various factors influencing performance. Besides macroeconomic policies and national strategies, companies in Indonesia must develop the capability to effectively engage their employees, fostering a work environment that promotes productivity and growth. The purpose of this research is to investigate the impact of job pressure and task complexity on performance, with a specific focus on the moderating role of resilience. This study employs Structural Equation Modeling (SEM) with the assistance of Smart PLS software to analyze the data. The Hair method was used to determine the appropriate sample size, resulting in a study involving 162 respondents from various industries. The research findings reveal several key insights. Firstly, job pressure does not have a direct impact on performance. This suggests that simply increasing job pressure will not necessarily lead to better performance outcomes. On the other hand, task complexity has a direct and significant influence on performance, indicating that employees tend to perform better when engaged in more complex and challenging tasks. Furthermore, the study highlights the critical role of resilience as a moderating factor. Specifically, resilience capacity moderates the relationship between job pressure and performance, as well as the relationship between task complexity and performance. This means that employees with higher resilience are better able to cope with job pressure and handle complex tasks more effectively, ultimately leading to improved performance. The implications of these findings are clear: companies need to focus on enhancing job complexity and strengthening their employees' resilience capabilities if they aim to improve overall performance. By doing so, they can create a more dynamic and productive workforce capable of sustaining high performance levels even in the face of challenges and pressures. This approach not only benefits individual companies but also contributes to the broader goal of maintaining and enhancing Indonesia's global competitiveness.